Estratégias competitivas e custos de transação no setor sucroalcooleiro: o caso Cosan - Pinto, Carlos Joaquim Paulino (2009)
The main goal of this thesis is to analyse the competitive strategies assumed by the mills of the sugar-ethanol sector in Center-South of Brazil facing the Institutional Environment change, as an example Cosan´s case study. This is made through the analysis of interaction between Institutional Environment and players, in the period of sector regulation and deregulation, and its effects under competitive environment. The thesis is divided in four fundamental parts: (i) the presentation of theoretical reference, which treats of the mean concepts of Institutional Economics and the Economics of Transaction Costs, and its relation with agroindustry; (ii) the sugar-ethanol industry overview in brazilian economy context; (iii) the analysis of the Institutional Environment from the regulation and deregulation sector process; and (iv) the analysis of how the sugar cane mills have rebuilt comprehending the new competitive strategies assumed, from the sector´s deregulation, focusing Cosan´s case, which is an example of player that it has adapted to the new environment conditions